Annual editions : (McGraw-Hill, 2011)
The Annual Editions series is designed to provide convenient, inexpensive access to a wide range of current articles from some of the most respected magazines, newspapers, and journals published today. Annual Editions are updated on a regular basis through a continuous monitoring of over 300 periodical sources. The articles selected are authored by prominent scholars, researchers, and commentators writing for a general audience. The Annual Editions volumes have a number of common organizational features designed to make them particularly useful in the classroom: a general introduction; an annotated table of contents; a topic guide; an annotated listing of selected World Wide Web sites; and a brief overview for each section. Each volume also offers an online Instructor's Resource Guide with testing materials. Using Annual Editions in the Classroom (available in print and online) is a general guide that provides a number of interesting and functional ideas for using Annual Editions readers in the classroom. Visit www.mhhe.com/annualeditions for more details.